2002
DOI: 10.1016/s0735-1097(02)02345-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of advanced atrial pacing therapies for atrial tachyarrhythmias in patients with a new implantable dual chamber cardioverter-defibrillator

Abstract: Atrial ATP therapies terminate many episodes of AT without ventricular proarrhythmia. The addition of 50-Hz Burst pacing has minimal efficacy for AT/AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…If ventricular rate falls within the VF detection window, appropriate therapy should not be withheld (see Section 7.6 for further discussion). Sophisticated algorithms enhance specificity of VT therapy and help to avoid VT therapies based on rate criteria alone (1012)(1013)(1014). Beta blockade is also a valuable therapy that will prevent many unwanted device interventions due to supraventricular arrhythmias.…”
Section: Supraventricular Tachyarrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation
“…If ventricular rate falls within the VF detection window, appropriate therapy should not be withheld (see Section 7.6 for further discussion). Sophisticated algorithms enhance specificity of VT therapy and help to avoid VT therapies based on rate criteria alone (1012)(1013)(1014). Beta blockade is also a valuable therapy that will prevent many unwanted device interventions due to supraventricular arrhythmias.…”
Section: Supraventricular Tachyarrhythmiasmentioning
confidence: 99%
“…High-rate atrial antitachycardia pacing may induce (transient) AF. Efficacy of advanced atrial pacing or cardioversion therapies varies greatly in function of episode duration, atrial cycle length, and atrial tachycardia mechanism (1013,1019,1020). Acute efficacy of atrial antitachycardia pacing may be as high as 40% (1013).…”
Section: Dual-chamber Implantable Cardioverter-defibrillatorsmentioning
confidence: 99%
“…Another strategy, anti-tachycardia pacing (ATP), seeks to avoid the development of permanent AF by suppressing paroxysmal AF. ATP consists of a train of 8-10 low-energy stimuli delivered as a pacing ramp or burst at 50Hz via a single pacing electrode 9. ATP is effective in treating spontaneous atrial tachyarrhythmias, especially slower tachycardias,9-10 but it is not very effective for converting AF 9,11-12…”
mentioning
confidence: 99%
“…Their AT/AF may be treated with a combined atrial and ventricular ICD. Atrial ATP has not been reported to cause ventricular proarrhythmia in patients who do not have either ventricular arrhythmias or significant structural heart disease 2–4 . These patients can be treated using an atrial antitachycardia pacemaker with low or minimal risk.…”
Section: Discussionmentioning
confidence: 99%